2011
DOI: 10.4103/0019-5359.108947
|View full text |Cite
|
Sign up to set email alerts
|

Needle stick injury and HIV risk among health care workers in North India

Abstract: Two-thirds of HCWs were exposed to needle stick injuries. Lack of awareness about post-exposure prophylaxis (PEP) was found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 15 publications
1
24
1
1
Order By: Relevance
“…Recapping has been mentioned as the major cause for NSI and second reason after blood collection as stated by Murlidhar, Ashat, Saleem. 2,13,15 58% students stated emergency ward had maximum chance to get NSI. Students have given various reasons for getting the NSI, such as 50 % of our students felt it happens due to lack of time, lack of assistance, fatigue.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Recapping has been mentioned as the major cause for NSI and second reason after blood collection as stated by Murlidhar, Ashat, Saleem. 2,13,15 58% students stated emergency ward had maximum chance to get NSI. Students have given various reasons for getting the NSI, such as 50 % of our students felt it happens due to lack of time, lack of assistance, fatigue.…”
Section: Discussionmentioning
confidence: 97%
“…9.14 Poor knowledge of healthcare workers on the PEP guidelines has been mentioned in few studies carried out previously. 11,12,15,16 In a study by Aminde though mentioned that 27% of medical students indeed knew the ideal PEP guidelines. 16 This observation was further supported by the findings of Saleem which observed that 33% postgraduate students and 19% doctors had exact knowledge on PEP and also the time of initiation of PEP.…”
Section: Discussionmentioning
confidence: 99%
“…Second, our model does not account for dynamic effects in terms of natural reduction in the prevalence of BBIs among the population in future years. Third, the pattern of unsafe (or safe) practices is dependent on the number of years of experience of a HCP and, so, NSI rates may vary with varying years of experience [95][96][97]. However, we considered an average risk of NSIs.…”
Section: Limitationsmentioning
confidence: 99%
“…The injury caused by needlestick and sharp objects while working in health care environments is one of the major health threats among the health care providers. This means that NSI and injuries caused by sharp objects such as blood-contaminated syringes and needles infected by patients' body fluids can seriously threaten the health of health care workers [1][2][3]. The most important complications cuased by these injuries are HIV, hepatitis B and hepatitis C virus infection [4][5][6].…”
Section: Introductionmentioning
confidence: 99%